Sr0.85Ce0.15Fe0.67Co0.33-xCuxO3 perovskite oxides: effect of B-site copper codoping on the physicochemical, catalytic and antibacterial properties upon UV or thermal activation - Tummino, Maria Laura; Vineis, Claudia; Varesano, Alessio; Liotta, Leonarda Francesca; Rigoletto, Monica; Laurenti, Enzo; Deganello, Francesca (Frontiers in Environmental Engineering, 2023)
Perovskite-type compounds have found application in environmental remediation and in clean energy production, fundamental sectors for sustainable development. A challenge for these materials is the fine-tuning of their chemical composition and their chemical-physical characteristics, for example, microstructure, morphology and ability to form oxygen vacancies, through the introduction of dopant elements. In this work, we studied the effect of Cu doping at the B-site of a Ce, Co-doped strontium ferrate perovskite with chemical composition Sr0.85Ce0.15Fe0.67Co0.33O3-δ. Indeed, Sr0.85Ce0.15Fe0.67Co0.23Cu0.10O3-δ and Sr0.85Ce0.15Fe0.67Co0.13Cu0.20O3-δ powders, where the B-site was codoped with both cobalt and copper, were synthesised by solution combustion synthesis and characterised for their physical-chemical properties by a multi-analytical approach, to assess their behaviour when subjected to different activation methods. The two codoped perovskites were tested i) as catalysts in the oxidation of soot after activation at high temperatures, ii) as antibacterial agents in ambient conditions or activated by both UV exposure and low-temperature excitation to induce the generation of reactive species. Results demonstrated that these compounds react differently to various stimuli and that the increasing amount of copper, together with the presence of segregated ceria phase, influenced the materials' features and performances. The knowledge gained on the structure-properties relationships of these materials can inspire other research studies on perovskite oxides application as multifunctional materials for the benefit of the environment, society and economy.